2021
DOI: 10.1080/23322039.2021.1954317
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between human capital and firm value: Evidence from Indian firms

Abstract: The purpose of this paper is to investigate whether human capital affects firm value by following a positive methodological approach. According to the classical theory of economic growth, the output of a country depends on its human and physical capital. At the micro-level, the same theory holds true for firm output. Thus, the human capital of a firm should play a significant role in firm performance and therefore firm valuation. Our results show a positive relationship between human capital and firm value. Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Al-Delawi et al (2023) have found that the increase in the company's market value is due to human capital and that the efficiency of the employees is high. Also, Sisodia et al (2021) confirmed a positive association between a company's value and human capital. These empirical findings confirm what Smith (1776) had recognized, i.e., that people's abilities, knowledge, and skills are the fundamental source of wealth.…”
Section: Other Determinants Of a Company's Valuementioning
confidence: 60%
“…Al-Delawi et al (2023) have found that the increase in the company's market value is due to human capital and that the efficiency of the employees is high. Also, Sisodia et al (2021) confirmed a positive association between a company's value and human capital. These empirical findings confirm what Smith (1776) had recognized, i.e., that people's abilities, knowledge, and skills are the fundamental source of wealth.…”
Section: Other Determinants Of a Company's Valuementioning
confidence: 60%
“…Studies on human capital in organisations focus on the way employees and managers accumulate knowledge and skills and how such stock of knowledge and skills enable organisations to improve performance (Timothy, 2022). Sisodia et al (2021) stated that it is difficult for a firm to create competitive advantage without efficient labour force, even when the firm has adequate financial resources, advanced technologies and sophisticated infrastructure. Human capital aids in the achievement of organizational goals with the overarching goal of fostering regional and national development.…”
Section: Human Capital Developmentmentioning
confidence: 99%
“…According to the human resources approach, employees are the most important resources of an organization (see: [35], [36]). The importance of human resources is emphasized both in classical and modern models of organization, where not only human resources are almost always among the basic elements of the organization, but also have a fundamental impact on the effectiveness of its functioning [37].…”
Section: B Job Performance As the Factor Influencing Organizational P...mentioning
confidence: 99%